IMPROVING MATHEMATICS LEARNING OUTCOMES OF CLASS IX MIDDLE SCHOOL STUDENTS IN THE MAJOR AREA AND FLAT BUILDING USING REALISTIC APPROACHES - Asep Yusuf; Ruslan Mubarok (Kopertis Region IV Jabar and Banten, 2020)
The problem of this research is how to apply realistic mathematics to the wide discussion and the circumference of flat shapes. The aim is to identify the difficulties of junior high school students in completing story questions in broad and rounded discussion. This research method is classroom action research. Subjects of the study included students of class IX-B at SMPN 1 Campaka Mulya. The instrument tested was a test sheet containing 5 questions in the form of a description. The study was conducted in three cycles, in each cycle consisting of several stages, namely planning, implementing actions, observing, and reflecting. From the results of the study obtained information related to improving student learning outcomes. This is known from the average value and percentage of mastery learning in each cycle that is increasing. In cycle I the average value is 53.8 with completeness of learning 3.7% and included in the category of inadequate, the average value of cycle II is 75.2 with mastery learning 40.7% and included in the category enough, and the average value the average cycle III is 82.8 with mastery learning reaching 92.5% or included in the Good category. After the implementation of the action, it appears that students become more happy and enthusiastic in learning mathematics by using a realistic approach to the broad discussion and the circumference of flat shapes.